GENDER DI SEPUTAR PERGELARAN WAYANG JEKDONG DALAM BUDAYA JAWA TIMURAN - Wisma Nugraha Christianto (Humaniora, 2009)
Using an ethnographic research technique, within aninterpretive framework, this study sought to understand genderrelations in some wayang Jekdong performances from the perspectiveof the members themselves. Using interviews and observation, theresearch was carried out continuously over a period several months.Having developed categories and established themes, the data wereinterpreted using the analytic narrative. The entry of women into thefields of wayang Jekdong performances has affected gender roles anddivision of labor within households. Men argue that, while manywomen can try to "have it all," societal expectations placed uponwomen preclude them from devoting themselves fully to domesticactivities and child-rearing. Several themes were identified from themass of raw data: (a) attitudes towards participation, (b) socialinteraction and communication, (c) organisation and compliance withrules and regulations, (d) age, (e) female and male voice. Womansand childrens gave a multitude of reasons for supporting some eventsof wayang Jekdong performance those were reflected in theirbehaviour within the communities. 'The atmosphere during women'sactivities preparing and enjoy to watching wayang Jekdongperformance is very light-hearted because all the women want is tohave fun and enjoy each other's. Women are able to laugh atthemselves and enjoy the experience.